Penyuluhan Hipertensi Sebagai Upaya Promotif dan Preventif di Desa Danguran RW 13 Kecamatan Klaten Selatan - Ramayani, Septiana Laksmi (Jurnal Dimas, 2025)
Hypertension is one of the health problems that is increasingly rising worldwide and is often referred to as a "silent killer."Hypertension often does not show clear symptoms, so many individuals are unaware of it, making it one of the causes of non-communicable diseases that can lead to serious complications such as stroke, heart disease, and kidney failure.Hypertension is defined as an increase in systolic blood pressure greater than or equal to 140 mmHg, and an increase in diastolic pressure greater than or equal to 90 mmHg.Promotive and preventive efforts for hypertension can be carried out through health education and health screening.This counseling can increase knowledge about hypertension, including risk factors, symptoms, and prevention methods.With the increase in knowledge, it is hoped that the community can be more proactive in maintaining their health and taking appropriate preventive measures.Community service activities were conducted in Danguran Village RW 13, Klaten Selatan District, Klaten Regency, Central Java.The activity was attended by 22 community members.The activity began with a pretest – distribution of material leaflets – presentation of material and demonstration of making traditional concoctions to lower blood pressure – posttest.Based on the community service activities conducted, there was an increase in the community's understanding of hypertension as a promotional and preventive effort.Out of the 20 questions given, 19 questions showed an increase in understanding and 1 question showed no change.Based on the level of understanding, there was an increase in the good category from the pretest and posttest scores by 40, resulting in an average increase in understanding of 40.91%.